BOLAJAQ OQÍTÍWShÍLARDA KREATIVLIK KÓZQARASLARDÍŃ RAWAJLANÍWÍ - Oraqbaev, Z.Z. (SCIENCE and SOCIETY, 2025)
The article examines the issues of forming the creative abilities of future pedagogues and providing proper education to students. Pedagogical skill, characteristics of cooperation with students were analyzed.